Influence of Tannin-PF resin ratio on impregnated papers - Ikmal Hisham, Izzwan Hafizi (2019)
Acacia mangium is a fast growing species that dominating the plantation in Malaysia. Tannin extracts from A. mangium tree bark were found to be rich in phenolic compounds and had the potential to replace synthetic adhesive used in the wood products industry. In this study, resin impregnated papers were prepared by impregnating filter paper with A. mangium tannin solution mixed with phenol formaldehyde at five different ratios which were 100:0, 70:30, 50:50, 30:70 and 0:100. These impregnated papers were then overlaid on a five ply plywood as a substrate. The aim of this study is to determine the effect of Tannin-PF resin ratio on the surface properties of the impregnated papers. Stain test, cross cut test and water vapour test were carried out to test the surface properties of the impregnated papers. The results show that resin impregnated paper with a 50:50 ratio of tannin-phenol formaldehyde resin gives an excellent results in all aspects compared to the other ratios.